Rotación de personal y desempeño laboral de los servidores públicos de la Gerencia Regional de Salud de Loreto año 2025 - Gomez Pizango, Natalia (2025)
The study "Staff turnover and job performance of public servants of the Regional Health Management of Loreto, year 2025" was conducted using a basic methodology with a quantitative approach, at a descriptive-correlational level, and with a non-experimental, cross-sectional design. The population consisted of 373 employees of the institution, with a sample of 190 participants selected through non-probabilistic convenience sampling. The general descriptive result showed that the majority perception among respondents placed staff turnover at 74% in the "some" level and job performance at 75% in the same category. At the inferential level, a moderate positive correlation was found with a Spearman's Rho = 0.514, which was statistically significant with a p < 0.05 between both variables. The general conclusion determined that a significant, positive relationship of moderate magnitude exists between staff turnover and job performance. The main recommendation was to design a Strategic Staff Turnover Management Plan that allows capitalizing on the positive relationship detected to improve organizational performance.